2011
DOI: 10.1007/s10620-011-1975-5
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular Intrahepatic Portosystemic Shunt for Portal Cavernoma with Symptomatic Portal Hypertension in Non-cirrhotic Patients

Abstract: TIPS procedures are feasible and safe in selected patients with portal cavernoma. Successful TIPS insertions may decrease the incidence of variceal rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 33 publications
1
86
2
1
Order By: Relevance
“…In addition, as for the cirrhotic patients undergoing transjugular intrahepatic portosystemic shunts for the management of variceal bleeding, a preexisting PVT was not associated with the risk of rebleeding. However, it should be noticeable that a transjugular intrahepatic portosystemic shunt becomes technically complex in the setting of complete PVT and even impossible when an occluded portal vein progresses into fibrotic cord [31,32]. Generally, these findings suggested that PVT should increase the risk of bleeding in liver cirrhosis in nearly all clinical conditions but after transjugular intrahepatic portosystemic shunt.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as for the cirrhotic patients undergoing transjugular intrahepatic portosystemic shunts for the management of variceal bleeding, a preexisting PVT was not associated with the risk of rebleeding. However, it should be noticeable that a transjugular intrahepatic portosystemic shunt becomes technically complex in the setting of complete PVT and even impossible when an occluded portal vein progresses into fibrotic cord [31,32]. Generally, these findings suggested that PVT should increase the risk of bleeding in liver cirrhosis in nearly all clinical conditions but after transjugular intrahepatic portosystemic shunt.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [5,13], PVT was diagnosed if there was a thrombus within the main portal vein, regardless of thrombus extension into the superior mesenteric vein or splenic vein. The extension of PVT was evaluated according to the imaging findings.…”
Section: Methodsmentioning
confidence: 99%
“…167 In chronic PVT (portal cavernoma) TIPS placement has been successful in 35%-80%. [168][169][170][171] TIPS is unsuccessful if the lumen of thrombosed portal vein is not catheterizable and cavernomatous vein is not amenable to dilatation.…”
Section: Tipsmentioning
confidence: 99%